Excellent Service with A Leadership Style Transformational Improves Customer Satisfaction - Robby Prayudha; Yunia Wardi (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
Current technological developments and digitalization demand that business people and companies continue to innovate. The urgency is not only the need to survive, but how to increase productivity, performance and profit. Effective leadership plays an important role in determining the success or failure of a company. Appropriate and effective leadership implementation including increasing consumer satisfaction. One alternative that is quite a solution that can be chosen by the leadership of a business owner or company is excellent service. This article is a conceptual article in the form of a literature study by examining several related articles. This paper is expected to explain about excellent service, transformational leadership styles, and the importance of these two things to consumer satisfaction. The characteristics of transformational leadership have the power to drive the potential that exists in the company. Transformational leadership that is carried out with leadership characteristics that are charismatic, inspiring, intellectual stimulus, and individual consideration is able to create effectiveness and efficiency in carrying out all excellent service indicators. Transformational leadership that is carried out with these characteristics is a strategic potential to achieve the goal of excellent service, namely increasing consumer satisfaction, including achieving consumer expectations, needs and desires.